2021
DOI: 10.1002/psp.2475
|View full text |Cite
|
Sign up to set email alerts
|

Migrant mothers, rejected refugees and excluded belonging in Hong Kong

Abstract: Building on ethnographic research and on studies of noncitizenship, this paper examines 'excluded belonging', a condition that is constructed over time, through a process of interactions between noncitizens and migratory assemblages. Noncitizens respond to the shifting parameters of inclusion and exclusion in their everyday lives in their attempts to construct a substantive sense of belonging that is often fleeting, fragile and ever challenged. Maintaining this condition entails work, learning, struggles and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…A study conducted in mainland China, where there is no specific visa category or immigration policy for MDWs, discussed MDWs' barriers to accessing care and other public services as a result of their undocumented or irregular immigrant status [35]. However, three studies conducted in Hong Kong described maternity protections stipulating that MDWs in Hong Kong cannot be terminated if they become pregnant, although enforcement appeared inconsistent [71,[111][112][113].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted in mainland China, where there is no specific visa category or immigration policy for MDWs, discussed MDWs' barriers to accessing care and other public services as a result of their undocumented or irregular immigrant status [35]. However, three studies conducted in Hong Kong described maternity protections stipulating that MDWs in Hong Kong cannot be terminated if they become pregnant, although enforcement appeared inconsistent [71,[111][112][113].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…MDWs appeared to be less reliant on organizations for support and access to resources than they were on social networks and family, though some did report seeking health-related, employment-related, and legal information from NGOs and churches [103,111,[148][149][150][151].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Immoral behavior towards strangers in the highly mobile Chinese society, such as queue jumping and ignoring elders who have fallen over, has been widely discussed in the media and academia (Schak, 2018). Anthropologist Nicole Constable's work (2021) also suggested that migrant workers experience “excluded belonging,” which involves trying to create, assert, and assimilate a state of shared meaning and belonging. Even though the transformation of social relations during the pandemic was primarily negative, social support was one positive factor among some workers (Clair et al., 2021).…”
Section: Diversified Moral Valuesmentioning
confidence: 99%
“…The articles all draw on detailed field research to bring into focus the common elements of exclusion that people across widely divergent citizenship status categories are subjected to. Indeed, whether seeking employment as refugees (Bélanger et al, 2021), struggling against deportation as temporary workers (Constable, 2021), managing the uncertainties of student visa status (Villegas, 2021), navigating the punitive control directed at domestic workers , or surviving the dehumanising punishments meted out in a detention centre (Montagne, this volume), all of these people are confronting myriad exclusions-from territory, status, rights, entitlements, and dignity-as central features of their migration process. By attending to these dynamics of systemic exclusion, the collection aims to further understanding the ways that growing global controls and limits on migration are operating today.…”
Section: Migrant Exclusionsmentioning
confidence: 99%